Implementasi Profetik Prenatal dan PAUD - Muhamad Fatih Rusydi (Universitas Al-Hikmah Indonesia, 2020)
This study aims to describe: 1) How is Prophetic Implementation in education? 2) What are the Prenatal and PAUD Education Stages? 3) How is the Prenatal and PAUD Prophetic Implementation? The data collection method is in the form of a literature study (library reseach) whose writing process uses the collection of books, journals and the results of several previous studies that support the theme of this authorship. The results showed: 1) In prophetic implementation into education, there is a character in someone who is very decisive for someone in self-development, both in terms of mental and moral aspects 2) Stages of prenatal education and early childhood education are a form of education that focuses on laying the foundation towards growth and development of both motor coordination (smooth and rough), emotional intelligence, plural intelligence (Multiple Intelligence) and spiritual intelligence. 3) Prophetic implementation in prenatal and PAUD is a form of parent stimulation to children such as parental assistance and supervision of what the child feels or hears.